2019
DOI: 10.1016/j.amsu.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and surgical approach of adult Hirschsprung's disease: About two observations and review of the literature. Case series

Abstract: IntroductionHirschsprung's disease (HD) is uncommon in adulthood. In this study, we describe the management of two cases of adult Hirschsprung's disease treated with transanal colonic pull-through procedure followed by a delayed coloanal anastomosis.Patients and methodsThis was a retrospective (December 2016 to Jun 2019) study included two cases of adult HD with confirmed Hirschsprung disease who underwent surgery at Zinder National hospital, Niger. The registration number is researchregistry 5174.ResultsThese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Diagnosis and treatment are conducted at an early age, in the first 5 years of life in more than 90% of cases. Consequently, the diagnosis of Hirschsprung’s disease in adulthood is rare [ 9 ]. The classic clinical symptoms including abdominal distension (in more than 90% cases), vomiting (more than 85% cases), which may be bilious, and failure to pass meconium during the first 24 h of life (more than 60% cases) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and treatment are conducted at an early age, in the first 5 years of life in more than 90% of cases. Consequently, the diagnosis of Hirschsprung’s disease in adulthood is rare [ 9 ]. The classic clinical symptoms including abdominal distension (in more than 90% cases), vomiting (more than 85% cases), which may be bilious, and failure to pass meconium during the first 24 h of life (more than 60% cases) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al, for example, mentions 300 reported cases up until 2006 [ 5 ], while Zhang and Ding [ 9 ], report 300 reported cases up until 2016 [ 9 ]. Adamou (2019) in his turn described a growth from 490 to 600 cases from 2009 till 2019 [ 10 ]. Part of this is due to the lack of medical access in certain parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal matter is palpable in over 50% due to fecal impaction being present in around 30% of the cases. In the study of Prato et al [ 13 ], he describes that 100% of his pediatric population with Hirschsprung’s disease presented with delayed meconium passage [ 5 , 8 , 10 ]. This is also noted in this literature review where Bakari et al [ 14 ], Ahmad et al [ 15 ], and Shitta et al [ 11 ] noted a history of delayed meconium passage in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, surgery can have good and satisfying outcomes by considering a less invasive technique using laparoscopic sigmoidorectal resection followed by a transanal lowering of the healthy colon without a stoma. This approach provides a better aesthetic and functional result than the techniques described above [ 17 ].…”
Section: Discussionmentioning
confidence: 99%